A method for preparing metal droplets
By assembling palindromic sequences into cross-shaped DNA nanostructures on gold nanoparticles, fluid metal droplets were prepared, solving the problem of preparing macroscopic multi-level structures and realizing high-order structures at the micrometer scale, which are suitable for biomimetic and chemical microreactors.
Patent Information
- Application Number
- CN202410184438.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-02-19
- Publication Date
- 2025-01-21
- Estimated Expiration
- 2044-02-19
AI Technical Summary
In the existing technology, the preparation of macroscopic multilevel structures regulated by weak molecular bonds has not been fully studied, and the development of functional materials with ordered structures in the liquid-liquid phase separation process is insufficient, making it difficult to prepare metal droplets with fluidity and responsiveness.
Metal droplets were prepared by assembling cross-shaped DNA nanostructures with palindromic sequences on gold nanoparticles and utilizing self-association in salt solution to form micron-sized high-order structures. Specific steps included mixing, centrifugation, washing, and oscillating incubation, using thiol-modified DNA and polyadenine DNA to form gold nanoparticle assemblies with sticky end sequences.
The prepared metal droplets exhibit liquid-phase-like properties, with excellent fluidity and flowability, and can form high-order structures at the micrometer size, making them suitable for applications such as bionics, sensing, and chemical microreactors.
Smart Images

Figure CN118045997B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of materials, and in particular to a method for preparing a metal droplet material. Background Art
[0002] In materials science, functional materials can be developed to meet specific applications, such as plasma, catalysts, drug delivery, and tissue engineering, through rational design and preparation of functional materials. The key to this challenge lies in the precise regulation of nanoscale preparation blocks. DNA, which is sequence-specific, programmable, and addressable, gives nanomaterials controllable bonding properties. Using DNA as a molecular bond, various nanoparticles can be assembled into complex structures, which helps to prepare a series of structures from nanometer to micrometer scales, each with unique physical and chemical properties. Spherical nucleic acids prepared based on gold nanoparticles (AuNPs) are nanomaterials composed of a gold nanoparticle core and a nucleic acid outer layer, which have been used to prepare solid crystals and superlattice structures. These structures are obtained by densely stacking in an ordered three-dimensional lattice using strong interactions between preparation blocks. However, the preparation of macroscopic multi-level structures regulated by weak molecular bonds remains to be studied.
[0003] Liquid-liquid phase separation processes are driven by multivalent interactions of polymers, supramolecules, proteins, nucleic acids, and other biomolecules, resulting in functional materials with ordered structures. Such liquid materials can contain a variety of functional components, including enzymes, drug molecules, or nanoparticles, and have excellent fluidity, responsiveness to external stimuli, and selectivity of molecular spacing, which enhances their properties and applications in biomimetics, sensing, therapy, and chemical microreactors. Therefore, the development of a new type of metal droplets will help to study the formation and dynamic properties of biomolecular structures in vivo as in vitro analogs. Summary of the invention
[0004] The purpose of the present invention is to overcome the shortcomings of the prior art, provide a method for preparing metal droplets, and deeply study the formation and dynamic properties of gold nanoparticle droplets, providing a new strategy for exploring functional liquid phase multi-level materials.
[0005] In order to achieve the purpose of the present invention, we will adopt the following technical solution to implement it.
[0006] 2. A method for preparing metal droplets, the method comprising the following steps:
[0007] S1. Adding n-butanol to the mixed solution containing DNA-AuNPs, with the volume ratio of the mixed solution to n-butanol being 1:3-15, rapidly vortex mixing, centrifuging for 5-10 seconds, and observing highly concentrated DNA-AuNPs dehydrated solid solution particles;
[0008] S2, add 0.5×TBE buffer solution to the solution obtained in S1, centrifuge for 5 to 10 seconds, the upper layer is n-butanol solution, and the lower layer is the obtained DNA-AuNPs;
[0009] S3, discard the upper n-butanol solution, continue to add 0.5×TBE buffer solution, centrifuge and wash, repeat twice, and resuspend in 0.5×TBE or ddH2O solution to obtain the assembled DNA-AuNPs;
[0010] Characterized in that the method for preparing the mixed solution containing DNA-AuNPs in S1 comprises the following steps:
[0011] S11. Under 4°C freezing conditions, concentrate the gold nanoparticle solution by centrifugation to 10-100 nM; dissolve the dry powder of four DNA chains used to form a cross-shaped DNA in enzyme-free water to dilute it into a DNA solution;
[0012] S12, mix the DNA solution in S11 in 10 mM Tris-HCl buffer solution, and the final concentration of each DNA chain is 20 μM;
[0013] S13, placing the solution obtained in S12 into a polymerase chain reaction thermal cycler, heating at 95° C. for five minutes, and then cooling to 4° C. to obtain a cross-shaped DNA nanostructure solution;
[0014] S14, mixing the gold nanoparticle solution obtained in S11 with the cross-shaped DNA nanostructure solution obtained in S13, wherein the molar ratio of the gold nanoparticles to the cross-shaped DNA nanostructure is 1:200-1000, adding a salt solution, and mixing uniformly to obtain a mixed solution containing DNA-AuNPs;
[0015] The method for preparing the metal droplets is to incubate the assembled DNA-AuNPs in S3 with a final concentration of 50 to 300 nM in a 100 to 350 mM sodium chloride solution at 37° C. for 1 hour under shaking to form gold nanoparticle droplets.
[0016] As a preferred embodiment of the present invention, the DNA in S1 includes: thiol-modified DNA and polyadenine DNA.
[0017] As a preferred embodiment of the present invention, the sequence length of the thiol-modified DNA is 36-38 nt, and the length of the polyadenine DNA is greater than 10 nt.
[0018] As a preferred embodiment of the present invention, the gold nanoparticles are spherical particles with a size of 5 nm and 10 nm, which are dispersed in an aqueous solution and whose surfaces are coated with citric acid molecules. The ultraviolet absorption peaks of the spherical gold nanoparticles of these two sizes are usually at 515-52 nm.
[0019] As a preferred embodiment of the present invention, the centrifugal condition of the gold nanoparticle solution in S11 is 10000-20000g.
[0020] As a preferred embodiment of the present invention, the four DNA chains in S11 include: C1 chain, C2 chain, C3 chain and C4 chain, wherein:
[0021] The sequence of the C1 chain is: CGCGAGCAAACAAGTCTACGAATCAATTCCCGTTGGC;
[0022] The sequence of the C2 chain is: CGCGGCCAACGGGAATTGAAATGAGAGGGTCTGTAATA;
[0023] The sequence of the C3 chain is: CGCGTATTACAGACCCTCTCAAACCGAGCATATGTCAG;
[0024] The sequence of the C4 chain is: CGCGCTGACATATGCTCGGAACGTAGACTTGTTTGCT.
[0025] As a preferred embodiment of the present invention, the salt solution in S14 is 1 mM TCEP.
[0026] As a preferred embodiment of the present invention, the mixed volume ratio of the mixed solution in S1 to n-butanol is preferably 1:9.
[0027] As a preferred embodiment of the present invention, the centrifugation condition in S1 is 1000-2000g.
[0028] Beneficial Effects
[0029] The beneficial effect of the present invention lies in that according to the method for preparing metal droplets provided by the present invention, through the cross-shaped DNA nanostructure with a palindromic sequence assembled on gold nanoparticles, these sticky end sequences can self-associate in a salt solution to assemble several gold nanoparticles into a high-order structure of micron size, and the prepared metal droplets exhibit liquid-like properties and have excellent fluidity. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 is a schematic diagram of the preparation method of the present invention;
[0031] Figure 2 The characterization of the cross-shaped DNA nanostructure by polyacrylamide gel electrophoresis in Example 1;
[0032] Figure 3The characterization of the assembled DNA-AuNPs using UV-visible / near-infrared spectrophotometer in Example 2;
[0033] Figure 4 The characterization of the assembled gold nanoparticle droplets using transmission electron microscopy in Example 3;
[0034] Figure 5 The laser scanning confocal microscope is used to characterize the assembled gold nanoparticle droplets in Example 4;
[0035] Figure 6 This is a test of photobleaching fluorescence recovery of the assembled gold nanoparticle droplets using a laser scanning confocal microscope in Example 5. DETAILED DESCRIPTION
[0036] The present invention is further described below in conjunction with specific examples. It should be understood that the following examples are only used to illustrate the present invention and are not used to limit the scope of the present invention.
[0037] All reagents of the present invention are commercially available. Gold nanoparticle solution was purchased from Xi'an Ruixi Biotechnology Co., Ltd., and all DNA sequences were commissioned to be synthesized by Sangon Biotechnology (Shanghai) Co., Ltd. The sequences used in this example are as follows:
[0038] DNA C1 (SEQ ID No. 1): CGCGAGCAAACAAGTCTACGAATCAATTCCCGTTGGC;
[0039] DNA C2 (SEQ ID No. 2): CGCGGCCAACGGGAATTGAAATGAGAGGGTCTGTAATA;
[0040] DNA C3 (SEQ ID No. 3): CGCGTATTACAGACCCTCTCAAACCGAGCATATGTCAG;
[0041] DNA C4 (SEQ ID No. 4): CGCGCTGACATATGCTCGGAACGTAGACTTGTTTGCT;
[0042] DNA C1-Cy3 (SEQ ID No. 5): CGCGAGCAAACAAGTCTACGAATCAATTCCCGTTGGC-Cy3;
[0043] DNA SH-A10-C4 (SEQ ID No. 6): SH-AAAAAAAAAACTGACATATGCTCGGAACGTAGACTTGTTTGCT;
[0044] DNA A10-C4 (SEQ ID No. 7): AAAAAAAAAACTGACATATGCTCGGAACGTAGACTTGT TTGCT;
[0045] DNA A30-C4 (SEQ ID No. 8):AAAAAAAAAAAAAAAAAAAAAAAAAAAACTGACATATGCTCGGAACGTAGACTTGTTTGCT.
[0046] As an embodiment of the present invention, Figure 1 As shown, a method for preparing metal droplets comprises the following steps:
[0047] S1. Adding n-butanol to the mixed solution containing DNA-AuNPs, with the volume ratio of the mixed solution to n-butanol being 1:9, rapidly vortex mixing, centrifuging for 5 to 10 seconds, and observing highly concentrated DNA-AuNPs dehydrated solid solution particles;
[0048] S2, add 0.5×TBE buffer solution to the solution obtained in S1, centrifuge for 5 to 10 seconds, the upper layer is n-butanol solution, and the lower layer is the obtained DNA-AuNPs;
[0049] S3, discard the upper n-butanol solution, continue to add 0.5×TBE buffer solution, centrifuge and wash, repeat twice, and resuspend in 0.5×TBE or ddH2O solution to obtain assembled DNA-AuNPs; wherein:
[0050] The method for preparing the mixed solution containing DNA-AuNPs in S1 comprises the following steps:
[0051] S11. Under 4°C freezing conditions, concentrate the gold nanoparticle solution by centrifugation to 50 nM; dissolve the dry powder of four DNA chains used to form a cross-shaped DNA in enzyme-free water to dilute it into a DNA solution;
[0052] S12, mix the DNA solution in S11 in 10 mM Tris-HCl buffer solution, and the final concentration of each DNA chain is 20 μM;
[0053] S13, placing the solution obtained in S12 into a polymerase chain reaction thermal cycler, heating at 95° C. for five minutes, and then cooling to 4° C. to obtain a cross-shaped DNA nanostructure solution;
[0054] S14, mixing the gold nanoparticle solution obtained in S11 with the cross-shaped DNA nanostructure solution obtained in S13, wherein the molar ratio of the gold nanoparticles to the cross-shaped DNA nanostructure is 1:500, adding a salt solution, and mixing well to obtain a mixed solution containing DNA-AuNPs;
[0055] The method for preparing the metal droplets is to incubate the assembled DNA-AuNPs in S3 with a final concentration of 200 nM in a 100-350 mM sodium chloride solution at 37° C. for 1 hour under shaking to form gold nanoparticle droplets.
[0056] As an embodiment of the present invention, Figure 1 As shown, the DNA in S1 includes: thiol-modified DNA and polyadenine DNA.
[0057] As an embodiment of the present invention, Figure 1 As shown, the sequence length of the thiol-modified DNA is 36 to 38 nt, and the length of the polyadenine DNA is greater than 10 nt.
[0058] As an embodiment of the present invention, Figure 1 As shown, the gold nanoparticles are spherical particles with a size of 5 nm and 10 nm, which are dispersed in an aqueous solution and whose surfaces are coated with citric acid molecules. The ultraviolet absorption peaks of the spherical gold nanoparticles of these two sizes are usually at 515-52 nm.
[0059] As an embodiment of the present invention, Figure 1 As shown, the centrifugal condition of the gold nanoparticle solution in S11 is 10000-20000g.
[0060] As an embodiment of the present invention, Figure 1 As shown, the four DNA chains in S11 include: C1 chain, C2 chain, C3 chain and C4 chain, wherein,
[0061] The sequence of the C1 chain is: CGCGAGCAAACAAGTCTACGAATCAATTCCCGTTGGC;
[0062] The sequence of the C2 chain is: CGCGGCCAACGGGAATTGAAATGAGAGGGTCTGTAATA;
[0063] The sequence of the C3 chain is: CGCGTATTACAGACCCTCTCAAACCGAGCATATGTCAG;
[0064] The sequence of the C4 chain is: CGCGCTGACATATGCTCGGAACGTAGACTTGTTTGCT.
[0065] As an embodiment of the present invention, Figure 1 As shown, the salt solution in S14 is 1 mM TCEP.
[0066] As an embodiment of the present invention, Figure 1 As shown, the mixing volume ratio of the mixed solution in S1 to n-butanol is preferably 1:9.
[0067] Characterization of cross-shaped DNA nanostructures by polyacrylamide gel electrophoresis
[0068] A 10% polyacrylamide gel was prepared and electrophoresed at 80 V for 100 minutes in a 1×TAEM buffer solution (40 mM Tris-acetate, 1 mM EDTA, 12.5 mM Magnesium acetate, pH 8.0-8.6) using a Bio-Rad electrophoresis instrument. After stopping the electrophoresis, the gel was stained in a solution containing 1×Gel Red nucleic acid dye for 10 to 15 minutes. The gel was imaged using a Tanon 2500B gel imaging analysis system to characterize the formation of DNA nanostructures.
[0069] The results are as follows Figure 2 As shown, the annealed DNA bands in lane 2 are mostly gathered in the gel pores, with a slow migration speed and high molecular weight, indicating the formation of a cross-shaped DNA nanostructure.
[0070] Preparation of DNA-AuNPs and UV-Vis / NIR Spectrophotometric Characterization
[0071] The gold nanoparticle solution was centrifuged and concentrated to the concentration shown in Table 1 below under 4°C freezing conditions, and the DNA powder was dissolved and diluted with enzyme-free water. DNA-AuNPs were assembled using the n-butanol rapid dehydration method. First, AuNPs and cross-shaped DNA solution were added to a 100 μL centrifuge tube according to the ratio shown in Table 1, and then an appropriate amount of salt solution was added. The present invention takes 1 mM TCEP as an example and mixed evenly. n-Butanol was added at a ratio of 1:9 to the mixed solution: n-Butanol for rapid vortex mixing to completely remove the water in the mixture. After a brief centrifugation for a few seconds, a highly concentrated DNA-AuNPs dehydrated "solid solution" can be observed. Subsequently, 10 μL of 0.5×TBE buffer solution (44.5 mM Tris, 1 mM EDTA, 44.5 mM bor ic acid, pH 8.0) was added to the above solution, and a brief centrifugation was performed at 2000 g for a few seconds. The lower layer was the obtained DNA-AuNPs. Finally, the upper butanol solution was discarded, and 0.5×TBE was added to wash the DNA-AuNPs by centrifugation. The whole process was repeated twice, and the DNA-AuNPs were resuspended in 0.5×TBE or ddH2O to obtain DNA-AuNPs.
[0072] DNA-AuNPs were supplemented with ddH2O to 100 μL, and all the ingredients were mixed by pipetting up and down. A UV-visible absorption spectrum was scanned in the wavelength range of 400 nm-700 nm to observe the changes in its absorption peak.
[0073] The results are as follows Figure 3 As shown, the UV absorption peak of DNA-AuNPs slightly red-shifted, which indicated that the cross-shaped DNA had been successfully assembled onto the gold nanoparticles.
[0074] Table 1 Assembly ratio
[0075]
[0076]
[0077] Transmission electron microscope image of a metal droplet
[0078] Prepare the sample for TEM. Drop 20 μL of about 5 μM metal droplet sample solution on the carbon film surface and let it adsorb for 2 minutes. Use absorbent paper to absorb the excess liquid of the sample. After the copper mesh is dried at room temperature, use Talos L120C G2 to image the sample at an accelerating voltage of 120 kV.
[0079] The results are as follows Figure 4 As shown, from Figure 4 It can be observed that the metal droplets are composed of a large number of gold nanoparticles, forming a highly dense spherical structure with a size of about 1 μm.
[0080] Laser scanning confocal microscopy characterization of metal droplets
[0081] Prepare samples for laser scanning confocal microscopy. Drop 20 μL of about 5 μM metal droplet sample solution in the confocal culture dish and allow it to adsorb for a few minutes. Characterize using Leica TCS SP8 STED 3X. Excite the metal droplets modified with Cy3 fluorescent molecules at 561 nm and record the emission spectrum at 570-650 nm.
[0082] Metal droplet samples such as Figure 5 As shown, it further demonstrates the formation of metal droplets, and that gold nanoparticles of different sizes (5 and 10 nm) and different types of cruciform DNA (thiol-modified and polyadenine-containing) can form metal droplets.
[0083] Fluorescence recovery experiment of metal droplets after photobleaching
[0084] After the metal droplets were formed, a laser scanning confocal microscope was used to perform a photobleaching fluorescence recovery experiment. Photobleaching was performed at 100% intensity for 20 seconds under a 561nm laser, resulting in a complete disappearance of the fluorescence in the target area. A series of images were acquired at a scanning rate of one frame per minute, and the recovery time was monitored for about 16 minutes until the fluorescence intensity reached a plateau. The average fluorescence intensity at different time points in the bleached area was recorded, and the fluorescence recovery curve was drawn based on the change, and a single exponential fit was performed using the Organic software.
[0085] The results showed that within the photobleaching region (white circle), the Cy3 fluorescence signal recovered quickly and completely, confirming that the metal droplets exhibited typical liquid phase behavior.
[0086] The above is only a preferred embodiment of the present invention, and is not intended to limit the scope of the present invention. The above embodiments of the present invention can also be modified in various ways. All simple, equivalent changes and modifications made according to the claims and the description of the present invention fall within the scope of protection of the claims of the present invention. The contents not described in detail in the present invention are all conventional technical contents.
[0087] The technical solution of the present invention is described in detail above in conjunction with the embodiments / drawings, but the present invention is not limited to the above technical solution. For ordinary technicians in this technical field, after knowing the contents recorded in the present invention, they can make several equivalent changes and substitutions without departing from the principle of the present invention. These equivalent changes and substitutions should also be regarded as belonging to the protection scope of the present invention.
Claims
1. A method for preparing metal droplets, the method comprising the following steps: S1. Adding n-butanol to the mixed solution containing DNA-AuNPs, with the volume ratio of the mixed solution to n-butanol being 1:3-15, rapidly vortex mixing, centrifuging for 5-10 seconds, and observing highly concentrated DNA-AuNPs dehydrated solid solution particles; S2, add 0.5×TBE buffer solution to the solution obtained in S1, centrifuge for 5 to 10 seconds, the upper layer is n-butanol solution, and the lower layer is the obtained DNA-AuNPs; S3, discard the n-butanol solution in the upper layer, continue to add 0.5×TBE buffer solution, centrifuge and wash, repeat twice, and resuspend in 0.5×TBE or ddH2O solution to obtain the assembled DNA-AuNPs; It is characterized in that The method for preparing the mixed solution containing DNA-AuNPs in S1 comprises the following steps: S11. Under 4°C freezing conditions, concentrate the gold nanoparticle solution by centrifugation to 10-100 nM; dissolve the dry powder of four DNA chains used to form a cross-shaped DNA in enzyme-free water to dilute it into a DNA solution; S12, mix the DNA solution in S11 in 10 mM Tris-HCl buffer solution, and the final concentration of each DNA chain is 20 μM; S13, placing the solution obtained in S12 into a polymerase chain reaction thermal cycler, heating at 95° C. for five minutes, and then cooling to 4° C. to obtain a cross-shaped DNA nanostructure solution; S14, mixing the gold nanoparticle solution obtained in S11 with the cross-shaped DNA nanostructure solution obtained in S13, wherein the molar ratio of the gold nanoparticles to the cross-shaped DNA nanostructure is 1:200-1000, adding a salt solution, and mixing uniformly to obtain a mixed solution containing DNA-AuNPs; The method for preparing the metal droplets is to incubate the assembled DNA-AuNPs in S3 with a final concentration of 50 to 300 nM in a 100 to 350 mM sodium chloride solution at 37° C. for 1 hour under shaking to form gold nanoparticle droplets.
2. The preparation method according to claim 1, characterized in that: The DNA in S1 includes: thiol-modified DNA and polyadenine DNA.
3. The preparation method according to claim 1, characterized in that: The gold nanoparticles in the gold nanoparticle solution in S11 are coated with citric acid.
4. The preparation method according to claim 3, characterized in that: The gold nanoparticles are spherical particles with a size of 5 nm and 10 nm.
5. The preparation method according to claim 1, characterized in that: The centrifugal condition of the gold nanoparticle solution in the S11 is 10000-20000g.
6. The preparation method according to claim 1, characterized in that: The four DNA chains in S11 include: C1 chain, C2 chain, C3 chain and C4 chain, wherein: The sequence of the C1 chain is: CGCGAGCAAACAAGTCTACGAATCAATTCCCGTTGGC; The sequence of the C2 chain is: CGCGGCCAACGGGAATTGAAATGAGAGGGTCTGTAATA; The sequence of the C3 chain is: CGCGTATTACAGACCCTCTCAAACCGAGCATATGTCAG; The sequence of the C4 chain is: CGCGCTGACATATGCTCGGAACGTAGACTTGTTTGCT.
7. The preparation method according to claim 1, characterized in that: The salt solution in the S14 is 1 mM TCEP.
8. The preparation method according to claim 1, characterized in that: The mixed volume ratio of the mixed solution in S1 to n-butanol is preferably 1:
9.
9. The preparation method according to claim 1, characterized in that: The centrifugal condition in S1 is 1000-2000g.
Citation Information
Patent Citations
Preparation method and application of metal-based DNA thermotropic liquid crystal
CN113560595A
Thermosensitive erasable plasmon polariton nanometer biological memory and preparation method thereof
CN114708886A